2019
DOI: 10.1126/scitranslmed.aav4176
|View full text |Cite
|
Sign up to set email alerts
|

Lysozyme elicits pain during nerve injury by neuronal Toll-like receptor 4 activation and has therapeutic potential in neuropathic pain

Abstract: The role of neuronal Toll-like receptor 4 (TLR4) in nerve injury is being pursued actively. However, the endogenous activation of neuronal TLR4 during neuroinflammation, in absence of the participation of glial TLR4, remains elusive. Here, we identified lysozyme as an endogenous activator of neuronal TLR4 signaling during nerve injury. Upon nerve injury, enhanced expression of lysozyme promoted neuronal hyperexcitability and neuropathic pain. Injections of lysozyme in healthy rats increased their mechanical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…Of note, recent work also reported the contribution of neuronal TLR4 in pain-related behavior after nerve injury in both male and female mice. 52 Thus, although HMGB1 is pronociceptive in both sexes and neuronal TLR4 seems to contribute to this, there may still be mechanistic aspects associated with differential actions on inflammatory cells that differ between sexes, in particular because it has been postulated that in the spinal cord, different nonneuronal cells contribute to sensitization in male and female mice, with microglia dominating this process in males and T cells in females. 43 Recently, we also reported that spinal glial inhibition reversed mechanical hypersensitivity in male, but not female, mice in the postinflammatory phase of the CAIA model.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, recent work also reported the contribution of neuronal TLR4 in pain-related behavior after nerve injury in both male and female mice. 52 Thus, although HMGB1 is pronociceptive in both sexes and neuronal TLR4 seems to contribute to this, there may still be mechanistic aspects associated with differential actions on inflammatory cells that differ between sexes, in particular because it has been postulated that in the spinal cord, different nonneuronal cells contribute to sensitization in male and female mice, with microglia dominating this process in males and T cells in females. 43 Recently, we also reported that spinal glial inhibition reversed mechanical hypersensitivity in male, but not female, mice in the postinflammatory phase of the CAIA model.…”
Section: Discussionmentioning
confidence: 99%
“…45 Lysozyme has also been recently shown to be involved in neuropathic pain. 46 These diverse actions could explain the purpose of LysM expression by adult neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al (2015) also used LPS-RS as a TLR4 antagonist in their SMR study, but they did not report if this antagonist had any effect on TLR4 expression. While LPS-RS is considered an LPS antagonist, its mechanism of action may not be related to TLR4 expression, but rather to the prevention of TLR4 signaling, which could also involve other molecules such as heat shock proteins (Cognasse et al, 2015;Gao and Li, 2016;Yadav and Surolia, 2019). Further studies in orofacial pain models are needed to address these possibilities.…”
Section: Discussionmentioning
confidence: 99%